Layer-by-layer alignment of silver nanowires for transparent and flexible energy-saving windows - Hu, Hebing (2022)
The energy consumption in buildings through the thermal radiation of windows has become a big challenge in modern life. The low mid-infrared emissivity (εMIR) and near-infrared blocking windows with high visible transmittance (Tvis) are highly required in modern energy-saving buildings, while most existing low εMIR windows are severely limited by their complex and high-cost processing conditions and could not be retrofitted to existing windows. Herein low εMIR foils based on aligned silver nanowires (AgNWs) fabricated via an economical solution process are reported with good energy-saving performance. The foils with aligned AgNWs give lower εMIR and higher Tvis compared with randomly oriented AgNWs foils. The low-cost process, high Tvis, low εMIR, and flexibility to apply on any surface opens a new avenue to cut down energy consumption in existing windows.